Strategy of Nematophagous Fungi in Determining the Activity of Plant Parasitic Nematodes and Their Prospective Role in Sustainable Agriculture - Al-Ani, Laith Khalil Tawfeeq; Soares, Filippe Elias de Freitas; Sharma, Ashutosh; de los Santos-Villalobos, Sergio; Valdivia-Padilla, Ana Victoria; Aguilar-Marcelino, Liliana (Frontiers in Fungal Biology, 2022)
In this review, we supply a framework for the importance of nematophagous fungi (nematophagous fungi [NF]) and their role in agricultural ecosystems. We characterize the taxonomy, diversity, ecology, and type of NF, depending on their interaction with plant-parasitic nematodes (PPNs). We described potential mechanisms of NF in the control of PPNs, the efficiency and methods of utilization, and the use of nematicides in sustainable agriculture. We explain the utilization of NF in nanotechnology as a new approach. NF are significant in the soil for having the effective potential for use in sustainable agriculture. These types of fungi belong to wide taxa groups, such as Ascomycota, Basidiomycota, and other groups. Diverse NF are available in different kinds of soil, especially in soils that contain high densities of nematodes. There is a relationship between the environment of nematodes and NF. NF can be divided into two types according to the mechanisms that affect nematodes. These types are divided into direct or indirect effects. The direct effects include the following: ectoparasites, endoparasites, cyst, or egg parasites producing toxins, and attack tools as special devices. However, the indirect effect comprises two groups: paralyzing toxins and the effect on the life cycle of nematodes. We explained the molecular mechanisms for determining the suitable conditions in brief and clarified the potential for increasing the efficacy of NF to highly impact sustainable agriculture in two ways: directly and indirectly.